Application Of Logistic Regression In Analysis Of Factors That Affect Implementation Of Electronic Medical Record - Agung Purwo Wicaksono; Kariyam Kariyam; Izzati Muhimmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Electronic Medical Record (EMR) has now become a trend in the world of health care. Lot of obstacles and barriers that interfere implementation of EMR. This paper discussed the eleven factors suspected to affect the implementation of EMR, with a case study hospital in Banyumas. By using logistic regression analysis obtained eight of the eleven factors that significantly affect the implementation of RME. The eight factors are financial factors, Human Resources (HR), the process of changing, psychological factors, legal factors, the time factor, organizational factors, and ICT trends. Technology, infrastructure, and social is a factor that does not significantly affect the implementation of EMR in hospital. ICT trends are new factors that significantly affect the implementation of EMR in hosital.